2022
DOI: 10.3390/polym14235321
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Optical Wavefront Technologies to Improve Patient Quality of Vision and Meet Clinical Requests

Abstract: Adaptive optics (AO) is employed for the continuous measurement and correction of ocular aberrations. Human eye refractive errors (lower-order aberrations such as myopia and astigmatism) are corrected with contact lenses and excimer laser surgery. Under twilight vision conditions, when the pupil of the human eye dilates to 5–7 mm in diameter, higher-order aberrations affect the visual acuity. The combined use of wavefront (WF) technology and AO systems allows the pre-operative evaluation of refractive surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…These values are comparable to those of poly(methyl methacrylate) (refractive index = 1.49 and Abbe number = 58), 78 and silicon and acrylic intraocular lenses (refractive index = 1.41-1.55 and Abbe number = 37-58). 79 These results implied that the AGluOH having hydrogen bonding ability can efficiently enhance the refractive index, while maintaining good transparency.…”
Section: Optical Propertiesmentioning
confidence: 89%
“…These values are comparable to those of poly(methyl methacrylate) (refractive index = 1.49 and Abbe number = 58), 78 and silicon and acrylic intraocular lenses (refractive index = 1.41-1.55 and Abbe number = 37-58). 79 These results implied that the AGluOH having hydrogen bonding ability can efficiently enhance the refractive index, while maintaining good transparency.…”
Section: Optical Propertiesmentioning
confidence: 89%
“…In addition to acids, ammonium hydroxide, as an alkaline-based treatment, has been used in conjunction with the detergent Triton X-100 to decellularize human corneas (Azevedo et al, 2018). This treatment combination effectively decellularized the tissue with little apparent effect on the collagen architecture and basement membrane proteins (Vacalebre et al, 2023). Nevertheless, ammonium hydroxide is also known to degrade growth factors and adversely alter the mechanical properties of the ECM.…”
Section: Chemical Techniques For the Decellularization Of Cornea 221 ...mentioning
confidence: 99%
“…Techniques that facilitate such characterizations rely on conventional histological and biochemical methods. Brightfield microscopy and hematoxylinbased DNA staining protocols are widely used for evaluating nuclear debris, and it is typically employed in conjunction with eosin to evaluate the fundamental ECM architecture of DCs (Sc et al, 2011;Fu and Hollick, 2023;Vacalebre et al, 2023). Fluorescent nuclear stains such as DAPI Gonzalez-Andrades et al, 2011;Shafiq et al, 2012), Hoechst (Amano et al, 2008;Wu et al, 2009;Corridon, 2022;Corridon, 2023c), and propidium iodide (Shafiq et al, 2012) are also frequently utilized.…”
Section: Removal Of Cellular Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has been developed in the astronomy field to add or remove aberration from the incident wavefront and allowing the telescope to boost image resolution by correcting the dynamic wavefront distortion caused by atmospheric turbulence. Owing to its benefits, AO is widely employed in the civil, industrial, and medical fields [14][15][16] and it has been demonstrated to improve laser processing material capabilities [17].…”
Section: Introductionmentioning
confidence: 99%